HIV seropositivity and sexuality: cessation of sexual relations among men and women living with HIV in five countries. (24th March 2016) - Bernier, Adeline; Lefèvre, Marie; Henry, Emilie; Verdes, Ludmila; Acosta, Maria-Elena; Benmoussa, Amal; Mukumbi, Henri; Cissé, Mamadou; Otis, Joanne; Préau, Marie
ABSTRACT: The sexuality of people living with HIV (PLHIV) is a key issue in the fight against HIV, as it influences both the dynamic of the epidemic and the quality of life of PLHIV. The present study examined the factors associated with cessation of sexual relations after HIV diagnosis among men and women in five countries: Mali, Morocco, Democratic Republic of the Congo, Romania and Ecuador. A community-based cross-sectional study was implemented by a mixed consortium [researchers/community-based organizations (CBO)]. Trained CBO members interviewed 1500 PLHIV in contact with CBOs using a 125-item questionnaire. A weighted multivariate logistic regression and a separate gender analysis were performed. Among the 1413 participants, 471 (33%) declared that they stopped having sexual relations after their HIV diagnosis, including 318 women (42%) and 153 men (23%) ( p  < .001). Concerning women, variables associated with the cessation of sexual relations in the final multivariate model were mainly related with relational factors and the possibility of getting social support (e.g., needing help to disclose HIV serostatus, feeling lonely every day, not finding support in CBOs, not being in a couple). Men's sexual activity was more associated with their representations and their perception of the infection (e.g., thinking they will have their HIV infection for the rest of their life, perceiving the HIV infection as a mystery, perceiving the infection as serious). Furthermore, the following variables were associated with both men and women sexual behaviours: being older, having suffered from serious social consequences after serostatus disclosure and not being able to regularly discuss about HIV with their steady partner. Results suggested clear differences between men and women regarding cessation of sexual relations and highlighted the importance of implementing gender-based tailored interventions that promote safe and satisfying sexuality, as it is known to have a positive impact on the overall well-being of PLHIV.